Resource utilization method of fluorine-containing sludge in photovoltaic wastewater
By adding calcium hydroxide and other additives to the photovoltaic wastewater sludge for flotation treatment, and mixing it with concrete slag and other materials to form, stable building materials bricks are formed, solving the problem of environmental secondary pollution caused by the dissolution of calcium fluoride sludge. , realize the resource utilization of sludge and the production of environmentally friendly building materials.
Patent Information
- Application Number
- CN202411156681.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Calcium fluoride sludge in photovoltaic wastewater sludge is difficult to stabilize and fix after treatment, resulting in dissolving under rainwater erosion and causing secondary environmental pollution. The existing technology has not effectively solved this problem.
By adding calcium hydroxide to the photovoltaic wastewater sludge for pre-treatment, combined with capture agent, foaming agent and regulator for flotation treatment, the impurities are removed and concrete slag, polymer, cement, nanotitanium dioxide, hollow nanocages are removed. The fiber materials are mixed, extruded and baked at high temperatures to form environmentally friendly building materials bricks, and the hollow nanocage fiber material is used to fix calcium fluoride to prevent it from dissolution.
It effectively solved the problem of sludge disposal, realized the resource utilization of sludge, and the building materials bricks formed have high mechanical strength, and prevented calcium fluoride from dissolution under rainwater erosion, avoiding secondary pollution in the environment.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater sludge recycling, and in particular to a method for resource utilization of fluorine-containing sludge from photovoltaic wastewater. Background Art
[0002] The photovoltaic industry and the semiconductor industry are developing rapidly, and the scale of the industry is expanding rapidly. There are a wide variety of fluorine raw materials and products based on fluorine raw materials, and fluorine pollution has also followed. Among them, solar panels use a large amount of hydrofluoric acid in the production process. The use of a large amount of hydrofluoric acid also produces a large amount of high-concentration fluorine-containing wastewater. In order to treat fluorine-containing wastewater, a large amount of inorganic fluorine-containing sludge will be produced. The composition of fluorine-containing sludge depends on the company's production process, raw and auxiliary materials, and products produced. Wastewater treatment mainly adopts chemical precipitation / coagulation treatment methods. Generally, it is neutralized first and then calcium chloride or calcium oxide is added to form a precipitate. There are also some that are first neutralized with calcium carbonate and then precipitated with flocculants. In addition to CaCO 3 , Ca(OH) 2 , CaCl 2 Calcium salts, SiO 2 , S, and P impurities, the main component is calcium fluoride. According to the "National List of Hazardous Wastes" (2016 edition), calcium fluoride sludge produced by wastewater treatment is no longer a hazardous waste. Although the "hydrofluoric acid etching solution treatment sludge" was removed from the list of hazardous wastes revised in 2016, the hazardous characteristics of calcium fluoride sludge still need to be identified and determined in accordance with the "Hazardous Waste Identification Standards". In addition, due to its low calorific value and high leaching risk, general disposal units will not accept it, resulting in an increasing stock of calcium fluoride sludge. With the development of science and technology, the demand for fluoride is increasing day by day, so the recycling of calcium fluoride sludge is imminent.
[0003] For example, Chinese patent CN106365610A discloses a method for making shale bricks from calcium fluoride sludge and a method for treating fluoride-containing wastewater. The method for making shale bricks from calcium fluoride sludge is to mix calcium fluoride sludge with a moisture content of less than 60% with shale, crush and grind it into a mixed dry powder with a particle size of less than 0.5 mm, and add fly ash; add water to mix, pile up and age, extrude to form blanks, and then burn the blanks to form shale bricks after drying; wherein the volume ratio of the mixed dry powder to the fly ash is 4:1-4:2; this provides a new method for treating calcium fluoride sludge and fluoride-containing wastewater, realizes the recycling of waste, and greatly improves the performance of the fired shale bricks; however, in the above technical scheme, the calcium fluoride sludge is not further treated, and since the calcium fluoride in the sludge has a certain solubility, the calcium fluoride in the bricks produced will gradually dissolve and release under the long-term scouring of rainwater, and flow into the surface through precipitation, causing secondary pollution to the soil, surface water and groundwater, and posing certain safety hazards. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for resource utilization of fluorine-containing sludge in photovoltaic wastewater. By treating the sludge in photovoltaic wastewater and then blending and extruding it with various materials, environmentally friendly building bricks can be obtained. The calcium fluoride in the building bricks is not easy to be lost, so it will not cause secondary pollution to the environment, thereby effectively solving the disposal problem of photovoltaic wastewater sludge.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for resource utilization of fluorine-containing sludge in photovoltaic wastewater, the specific method is as follows:
[0007] S1 adds calcium hydroxide to the sludge of photovoltaic wastewater, stirs it to make it fully mixed, and obtains pretreated sludge;
[0008] The amount of calcium hydroxide added is 8-12% of the total mass of the sludge;
[0009] S2 prepares the pretreated sludge into pulp, and then mixes and stirs it with a capture agent, a foaming agent and a regulator for flotation treatment;
[0010] The mass ratio of the capture agent, the foaming agent and the regulator is (2.0-2.3):1:(0.7-0.9);
[0011] The capture agent accounts for 0.1-0.3% of the mass of the pretreated sludge dry basis;
[0012] The flotation treatment has a temperature of 36-42°C and a flotation time of 6-12 minutes;
[0013] S3 The calcium fluoride sludge obtained by flotation is mixed with a strong acid solution to remove impurities soluble in the acid solution, and then neutralized with an alkali solution to obtain calcium fluoride sludge;
[0014] The strong acid solution is any one of hydrochloric acid and sulfuric acid;
[0015] The mass ratio of the calcium fluoride sludge to the strong acid solution is 1:(3-5);
[0016] S4: after mixing and grinding the concrete slag, the concrete slag is fully mixed with calcium fluoride sludge, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and water, extruded into a shape, dried and then baked at high temperature to obtain a building brick;
[0017] The mass ratio of the calcium fluoride sludge, concrete slag, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and water is (50-80): (20-30): (10-18): (40-50): (3-7): (5-9): (10-18): (8-15).
[0018] As a further preferred embodiment of the present invention, the capture agent is at least one of oleic acid, sodium alkyl sulfate, and sodium cyclopentaneate;
[0019] The foaming agent is at least one of pine oil, methyl isobutyl carbinol and butyl ether oil;
[0020] The regulator is composed of calcium chloride, acidified water glass, sodium carbonate and polyacrylamide in a mass ratio of 1: (0.2-0.4): (0.5-0.8): (0.6-0.9);
[0021] The high molecular polymer is composed of EVA emulsion and water-based chloroprene rubber in a mass ratio of 1: (1.0-1.3).
[0022] As a further preferred embodiment of the present invention, the temperature conditions for high temperature baking are as follows: the starting temperature is room temperature, which is increased to 800-860°C at a rate of 10-13°C / min, kept at that temperature for 30-50min, then cooled to 320-340°C at a rate of 12-15°C / min, and then cooled naturally.
[0023] As a further preferred embodiment of the present invention, the hollow nano cage fiber material is prepared by the following method:
[0024] 1) Dissolving cobalt nitrate hexahydrate and 2-methylimidazole in methanol respectively, mixing the two rapidly after dissolution, stirring for 30-50 minutes, and then standing at room temperature for 24-28 hours, collecting the precipitate by vacuum filtration, and repeatedly washing with methanol, and drying to obtain a porous skeleton material;
[0025] 2) The porous skeleton material and nickel nitrate hexahydrate are dispersed in anhydrous ethanol respectively, stirred sufficiently and then quickly mixed, placed in a reaction kettle, reacted at 120-125° C. for 2-5 hours, cooled to room temperature after the reaction is completed, the product is collected by vacuum filtration, repeatedly washed with ethanol, and dried to obtain a composite porous skeleton material;
[0026] 3) dispersing the composite porous skeleton material in the mixed solution, adding the composite fiber material, ultrasonically treating for 20-30 minutes, condensing and refluxing at 90-95° C. for 20-30 minutes, collecting the precipitate by vacuum filtration, repeatedly washing with ethanol and drying, and then obtaining the hollow nanocage fiber material.
[0027] Furthermore, the ratio of cobalt nitrate hexahydrate, 2-methylimidazole, and methanol is (1-2) mol: (4-8) mol: (150-260) mL;
[0028] The ratio of the porous skeleton material, nickel nitrate hexahydrate and anhydrous ethanol is (5-10) g: (10-20) g: (120-180) mL;
[0029] The ratio of the composite porous skeleton material, the mixed solution, and the composite fiber material is (2-5) g: (150-260) mL: (10-18) g;
[0030] The mixed solution is composed of anhydrous ethanol and deionized water in a volume ratio of (3-4):1.
[0031] As a further preferred embodiment of the present invention, the composite fiber material is prepared by the following method:
[0032] 1) Adding polyacrylonitrile to N,N-dimethylformamide, stirring at room temperature for 4-6 hours, then adding polypyrrole, continuing stirring for 48-52 hours, then adding modified composite nanoparticles, fully mixing to obtain a spinning solution, then electrospinning, drying, and carbonizing at 700-800° C. for 2-3 hours under nitrogen protection to obtain a nanofiber material;
[0033] 2) adding titanium tetrachloride to deionized water, then adding the nanofiber material after repeated washing and drying with distilled water, acetone and ethanol, treating in a 70-75° C. water bath for 30-50 min, then placing in a muffle furnace, calcining at 500-560° C. for 30-50 min, to obtain a pretreated nanofiber material;
[0034] 3) Add tetrabutyl titanate to concentrated hydrochloric acid, then add distilled water, stir thoroughly, add pretreated nanofiber material, place in a reactor, stir at 50-80 r / min at 150-160° C. for 3-5 hours, cool to room temperature after the reaction, wash repeatedly with distilled water and anhydrous ethanol, dry, place in a muffle furnace, and calcine at 500-560° C. for 30-50 minutes to obtain a composite fiber material.
[0035] Furthermore, the ratio of polyacrylonitrile, N,N-dimethylformamide, polypyrrole, and modified composite nanoparticles is (10-20) g: (100-200) mL: (1-2) g: (1-2) g;
[0036] The electrospinning process is carried out under the following conditions: electrostatic voltage 18-24 kV, receiving distance 15-18 cm, and propulsion rate 2-3 mL / h.
[0037] Furthermore, the ratio of titanium tetrachloride, deionized water, and nanofiber material is (8-12) mL: (100-160) mL: (3-6) g;
[0038] The titanium tetrachloride has a concentration of 80-100 mmol / L;
[0039] The ratio of tetrabutyl titanate, concentrated hydrochloric acid, distilled water and pretreated nanofiber material is (1.5-2.8) mL: (50-80) mL: (50-80) mL: (2-5) g.
[0040] As a further preferred embodiment of the present invention, the modified composite nanoparticles are prepared by the following method:
[0041] 1) Dissolve zinc chloride, indium chloride tetrahydrate and thioacetamide in deionized water in turn, transfer to a reaction kettle after sufficient stirring, react at 180-186° C. for 10-15 hours, cool to room temperature, wash the product repeatedly with deionized water and anhydrous ethanol in turn, and dry to obtain flower-ball-shaped zinc thioindate;
[0042] 2) Dispersing zinc thioindate and nano-titanium dioxide in deionized water, ultrasonically dispersing for 30-50 minutes, mechanically stirring for 3-5 hours, centrifuging, and then repeatedly washing with deionized water and anhydrous ethanol, and then calcining at 160-165° C. for 2-3 hours to obtain composite nanoparticles with hydrangea-like structure;
[0043] 3) Anhydrous ethanol is measured and placed in a container, deionized water and glacial acetic acid are added, and the container is placed on a magnetic stirrer. KH570 is added dropwise while stirring for a hydrolysis reaction of 30-50 minutes. After the reaction is completed, the composite nanoparticles are added and reacted at 70-75° C. for 6-8 hours. After the reaction is completed, the product is repeatedly centrifuged and washed with anhydrous ethanol, and then dried to obtain modified composite nanoparticles.
[0044] Furthermore, the ratio of zinc chloride, indium chloride tetrahydrate, thioacetamide, and deionized water is (1.3-1.8) g: (5.8-6.5) g: (3.0-36.) g: (600-800) mL;
[0045] The ratio of the zinc thioindate, nano-titanium dioxide and deionized water is (2-5) g: (0.5-1.2) g: (500-800) mL;
[0046] The ratio of anhydrous ethanol, deionized water, glacial acetic acid, KH570 and composite nanoparticles is (100-150) mL: (10-18) mL: (8-13) mL: (2-3) mL: (2-3) g.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] In the present invention, calcium hydroxide is added to the sludge of photovoltaic wastewater, and calcium ions are combined with fluorine ions to generate calcium fluoride precipitation in a strong alkaline environment to remove free fluorine ions in the sludge. After pulping, the sludge is mixed and stirred with a capture agent, a foaming agent and a regulator for flotation, and treated with a strong acid solution to remove impurities. After neutralization with an alkali solution, calcium fluoride sludge is obtained, and then the sludge is fully mixed with concrete slag, a high molecular polymer, cement, a water reducing agent, nano titanium dioxide, a hollow nano cage fiber material and water, and then extruded and baked at high temperature to obtain building bricks that can be used in the construction industry, thereby effectively solving the problem of sludge disposal and realizing the resource utilization of sludge.
[0049] At the same time, in order to prevent the calcium fluoride contained in the building brick from being gradually dissolved and released during long-term use due to the influence of the environment, thereby causing secondary pollution to the environment, a specially prepared hollow nano cage fiber material is introduced into the building brick matrix in the present invention; the hollow nano cage fiber material first uses zinc chloride, indium chloride tetrahydrate and thioacetamide as raw materials, and obtains zinc thioindate with a flower ball structure having a large specific surface area through a hydrothermal reaction, and then adopts a stirring-ultrasound-calcination method to disperse nano titanium dioxide particles on the flower balls of the zinc thioindate, thereby increasing the size of the zinc thioindate. The surface roughness of the zinc flower ball structure is improved, thereby obtaining composite nanoparticles with a hydrangea-like structure having a large specific surface area and a large surface roughness, and then the composite nanoparticles are surface-modified by a silane coupling agent to improve the interfacial bonding force between the composite nanoparticles and the polymer, and to improve the stability of the composite nanoparticles in the polymer; then polypyrrole and polyacrylonitrile are mixed, and the modified composite nanoparticles are added and fully mixed to obtain a spinning solution, and a nanofiber material is obtained after electrostatic spinning, and after carbonization treatment, the polymer contained in the nanofiber material is burned. Carbonization, partially modified composite nanoparticles are exposed, so that the surface of the formed nanofiber material has a large number of composite nanoparticles with hydrangea-like structure, which are pre-cleaned, placed in a titanium tetrachloride solution for water bath treatment and then calcined, and tetrabutyl titanate is used as a titanium source, and a large number of nanorods are deposited on the surface of the nanofiber material after hydrothermal reaction and calcination. In addition, since the composite nanoparticles on the surface of the nanofiber material have a large specific surface area, sufficient sites are provided for the deposition of nanorods. At the same time, the composite nanoparticles have a large surface roughness, which increases the contact area with the nanorods, thereby enhancing the interface bonding strength between the two, so that the nanorods deposited on the surface of the nanofiber material are not easy to detach and the structure is stable; finally, the synthesized porous skeleton material is used as a template and the composite fiber material is used as a matrix. Since the nanorods deposited on the surface of the composite fiber material are shaped like thorn structures, they are easy to embed into the holes, so that the composite porous skeleton material obtained by in-situ growth on the template can be well inserted into the nanorods in the matrix, so that a strong bond can be formed between the two, thereby obtaining a hollow nanocage fiber material;
[0050] By introducing it into building brick materials, the hollow nanocage fiber material is constructed to form a network structure through the mutual entanglement between the fiber matrix, which helps to improve the mechanical strength of the building bricks on the one hand. At the same time, with the formation of the network structure, the hollow nanocages with a dodecahedral morphology and a porous hollow structure will also be distributed in large quantities in the building bricks, thereby forming a multi-level hollow nanocage continuum, which plays a role in extending the movement path and increasing the movement friction; when the calcium fluoride in the building bricks is dissolved with rainwater, the calcium fluoride will continuously encounter the hollow nanocages in the migration path, and thus will be embedded in the holes of the hollow nanocages. As the calcium fluoride continues to accumulate, it is confined in the holes and cannot continue to move, so that the calcium fluoride cannot be separated from the building brick matrix, thereby effectively avoiding the secondary pollution of the building bricks to the environment.
[0051] In the present invention, after the sludge of photovoltaic wastewater is treated, it is mixed and extruded with concrete residue, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and the like to obtain environmentally friendly building bricks, and the calcium fluoride in the building bricks is not easy to be lost, so it will not cause secondary pollution to the environment, thereby effectively solving the disposal problem of photovoltaic wastewater sludge. DETAILED DESCRIPTION
[0052] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] In the embodiment of the present invention, the capture agent is sodium alkyl sulfate; the foaming agent is methyl isobutyl carbinol; the regulator is composed of calcium chloride, acidified water glass, sodium carbonate and polyacrylamide in a mass ratio of 1:0.3:0.7:0.9; the high molecular polymer is composed of EVA emulsion and water-based chloroprene rubber in a mass ratio of 1:1.3.
[0054] In the embodiment of the present invention, the temperature conditions for high temperature baking are: the starting temperature is room temperature, the temperature is increased to 850°C at a rate of 10°C / min, kept at that temperature for 40 minutes, then cooled to 320°C at a rate of 13°C / min, and then cooled naturally.
[0055] Example 1
[0056] A method for resource utilization of fluorine-containing sludge in photovoltaic wastewater, the specific method is as follows:
[0057] S1 adds calcium hydroxide to the sludge of photovoltaic wastewater, stirs it to make it fully mixed, and obtains pretreated sludge;
[0058] The amount of calcium hydroxide added is 8% of the total mass of the sludge;
[0059] S2 prepares the pretreated sludge into pulp, and then mixes and stirs it with a capture agent, a foaming agent and a regulator for flotation treatment;
[0060] The mass ratio of the capture agent, the foaming agent and the regulator is 2.0:1:0.7;
[0061] The capture agent accounts for 0.1% of the mass of the pretreated sludge dry basis;
[0062] Flotation treatment, temperature 36 °C, flotation time 6 min;
[0063] S3 The calcium fluoride sludge obtained by flotation is mixed with a hydrochloric acid solution to remove impurities soluble in the acid solution, and then neutralized with an alkali solution to obtain calcium fluoride sludge;
[0064] The mass ratio of calcium fluoride sludge to hydrochloric acid solution is 1:3;
[0065] S4: after mixing and grinding the concrete slag, the concrete slag is fully mixed with calcium fluoride sludge, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and water, extruded into a shape, dried and then baked at high temperature to obtain a building brick;
[0066] The mass ratio of calcium fluoride sludge, concrete slag, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and water is 50:20:10:40:3:5:10:8.
[0067] The preparation method of the hollow nano cage fiber material is as follows:
[0068] 1) 1.3 g of zinc chloride, 5.8 g of indium chloride tetrahydrate and 3.0 g of thioacetamide were dissolved in 600 mL of deionized water, stirred thoroughly and transferred to a reactor, reacted at 180° C. for 10 h, cooled to room temperature, and the product was repeatedly washed with deionized water and anhydrous ethanol, and dried to obtain flower-ball-shaped zinc thioindate;
[0069] 2) 2 g of zinc thioindate and 0.5 g of nano-titanium dioxide were dispersed in 500 mL of deionized water, subjected to 200 W ultrasonic dispersion for 30 min, and then mechanically stirred at 500 r / min for 3 h. After centrifugation, the mixture was repeatedly washed with deionized water and anhydrous ethanol, and then calcined at 160 ° C for 2 h to obtain composite nanoparticles with a hydrangea-like structure.
[0070] 3) 100 mL of anhydrous ethanol was measured and placed in a container, 10 mL of deionized water and 8 mL of glacial acetic acid were added, and the container was placed on a magnetic stirrer. While stirring, 2 mL of KH570 was added dropwise for a 30-min hydrolysis reaction. After the reaction was completed, 2 g of composite nanoparticles were added and reacted at 70° C. for 6 h. After the reaction was completed, the product was repeatedly centrifuged and washed with anhydrous ethanol, and vacuum dried at 60° C. for 12 h to obtain modified composite nanoparticles;
[0071] 4) Add 10 g of polyacrylonitrile to 100 mL of N,N-dimethylformamide, stir at 150 r / min for 4 h at room temperature, then add 1 g of polypyrrole, continue stirring for 48 h, then add 1 g of modified composite nanoparticles, mix thoroughly to obtain a spinning solution, then perform electrostatic spinning under the conditions of an electrostatic voltage of 18 kV, a receiving distance of 15 cm, and a propulsion rate of 2 mL / h, and after drying, perform carbonization treatment at 700 ° C for 2 h under nitrogen protection to obtain a nanofiber material;
[0072] 5) 8 mL of titanium tetrachloride with a concentration of 80 mmol / L was added to 100 mL of deionized water, and then 3 g of nanofiber material was repeatedly washed and dried with distilled water, acetone and ethanol, and then added thereto, treated in a 70° C. water bath for 30 min, and then placed in a muffle furnace and calcined at 500° C. for 30 min to obtain a pretreated nanofiber material;
[0073] 6) 1.5 mL of tetrabutyl titanate was added to 50 mL of concentrated hydrochloric acid, and then 50 mL of distilled water was added. After sufficient stirring, 2 g of pretreated nanofiber material was added, and the mixture was placed in a reactor, and the mixture was stirred at 50 r / min and kept at 150° C. for 3 h. After the reaction was completed, the mixture was cooled to room temperature, washed repeatedly with distilled water and anhydrous ethanol, and dried. The mixture was placed in a muffle furnace and calcined at 500° C. for 30 min to obtain a composite fiber material.
[0074] 7) Dissolve 1 mol of cobalt nitrate hexahydrate and 4 mol of 2-methylimidazole in 150 mL of methanol respectively. After dissolution, mix the two quickly, stir at 300 r / min for 30 min, and then stand at room temperature for 24 h. Collect the precipitate by vacuum filtration, wash it repeatedly with methanol, and dry it at 60° C. in vacuum overnight to obtain a porous skeleton material;
[0075] 8) 5 g of the porous framework material and 10 g of nickel nitrate hexahydrate were dispersed in 120 mL of anhydrous ethanol respectively, stirred thoroughly and then quickly mixed, placed in a reaction kettle, reacted at 120° C. for 2 h, cooled to room temperature after the reaction was completed, the product was collected by vacuum filtration, repeatedly washed with ethanol, and dried to obtain a composite porous framework material;
[0076] 9) 2 g of the composite porous skeleton material was dispersed in 150 mL of a mixture of anhydrous ethanol and deionized water in a volume ratio of 3:1, and then 10 g of the composite fiber material was added. After ultrasonic treatment at 300 W for 20 min, the mixture was condensed and refluxed at 90 ° C for 20 min. The precipitate was collected by vacuum filtration, repeatedly washed with ethanol, and then dried to obtain a hollow nanocage fiber material.
[0077] Example 2
[0078] A method for resource utilization of fluorine-containing sludge in photovoltaic wastewater, the specific method is as follows:
[0079] S1 adds calcium hydroxide to the sludge of photovoltaic wastewater, stirs it to make it fully mixed, and obtains pretreated sludge;
[0080] The amount of calcium hydroxide added is 10% of the total mass of the sludge;
[0081] S2 prepares the pretreated sludge into pulp, and then mixes and stirs it with a capture agent, a foaming agent and a regulator for flotation treatment;
[0082] The mass ratio of the capture agent, foaming agent and regulator is 2.1:1:0.8;
[0083] The capture agent accounts for 0.2% of the mass of the pretreated sludge dry basis;
[0084] Flotation treatment, temperature 40°C, flotation time 10 min;
[0085] S3 The calcium fluoride sludge obtained by flotation is mixed with a hydrochloric acid solution to remove impurities soluble in the acid solution, and then neutralized with an alkali solution to obtain calcium fluoride sludge;
[0086] The mass ratio of calcium fluoride sludge to hydrochloric acid solution is 1:4;
[0087] S4: after mixing and grinding the concrete slag, the concrete slag is fully mixed with calcium fluoride sludge, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and water, extruded into a shape, dried and then baked at high temperature to obtain a building brick;
[0088] The mass ratio of calcium fluoride sludge, concrete slag, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and water is 60:25:14:45:5:7:15:12.
[0089] The preparation method of the hollow nano cage fiber material is as follows:
[0090] 1) 1.5 g of zinc chloride, 6.2 g of indium chloride tetrahydrate and 3.4 g of thioacetamide were dissolved in 700 mL of deionized water, stirred thoroughly and transferred to a reactor, reacted at 182° C. for 13 h, cooled to room temperature, and the product was repeatedly washed with deionized water and anhydrous ethanol, and dried to obtain flower-ball-shaped zinc thioindate;
[0091] 2) 3.5 g of zinc thioindate and 0.9 g of nano-titanium dioxide were dispersed in 700 mL of deionized water, subjected to 260 W ultrasonic dispersion for 40 min, and then mechanically stirred at 700 r / min for 4 h. After centrifugation, the mixture was repeatedly washed with deionized water and anhydrous ethanol, and then calcined at 163 ° C for 2.5 h to obtain composite nanoparticles with hydrangea-like structure.
[0092] 3) 130 mL of anhydrous ethanol was measured and placed in a container, 15 mL of deionized water and 11 mL of glacial acetic acid were added, and the container was placed on a magnetic stirrer. While stirring, 2.5 mL of KH570 was added dropwise for a 40-min hydrolysis reaction. After the reaction was completed, 2.5 g of composite nanoparticles were added and reacted at 72° C. for 7 h. After the reaction was completed, the product was repeatedly centrifuged and washed with anhydrous ethanol, and vacuum dried at 63° C. for 15 h to obtain modified composite nanoparticles;
[0093] 4) Add 15 g of polyacrylonitrile to 150 mL of N,N-dimethylformamide, stir at 180 r / min for 5 h at room temperature, then add 1.5 g of polypyrrole, continue stirring for 50 h, then add 1.5 g of modified composite nanoparticles, mix thoroughly to obtain a spinning solution, then perform electrostatic spinning under the conditions of an electrostatic voltage of 20 kV, a receiving distance of 16 cm, and a propulsion rate of 2.5 mL / h, and after drying, perform carbonization treatment at 750°C for 2.5 h under nitrogen protection to obtain a nanofiber material;
[0094] 5) adding 10 mL of titanium tetrachloride with a concentration of 90 mmol / L into 150 mL of deionized water, and then adding 5 g of nanofiber material which has been repeatedly washed and dried with distilled water, acetone and ethanol in sequence, to the water, treating it in a 72° C. water bath for 40 min, and then placing it in a muffle furnace and calcining it at 530° C. for 40 min to obtain a pretreated nanofiber material;
[0095] 6) Add 2.1 mL of tetrabutyl titanate to 70 mL of concentrated hydrochloric acid, then add 70 mL of distilled water, stir thoroughly, add 3 g of pretreated nanofiber material, place in a reactor, stir at 60 r / min and react at 155 ° C for 4 h, cool to room temperature after the reaction, wash repeatedly with distilled water and anhydrous ethanol, dry, place in a muffle furnace, and calcine at 530 ° C for 40 min to obtain a composite fiber material;
[0096] 7) 1.5 mol of cobalt nitrate hexahydrate and 6 mol of 2-methylimidazole were dissolved in 210 mL of methanol respectively. After dissolution, the two were quickly mixed and stirred at 400 r / min for 40 min. After standing at room temperature for 26 h, the precipitate was collected by vacuum filtration, repeatedly washed with methanol, and vacuum dried at 70° C. overnight to obtain a porous skeleton material;
[0097] 8) 7 g of the porous framework material and 15 g of nickel nitrate hexahydrate were dispersed in 150 mL of anhydrous ethanol respectively, stirred thoroughly and then quickly mixed, placed in a reaction kettle, reacted at 121° C. for 3 h, cooled to room temperature after the reaction was completed, the product was collected by vacuum filtration, repeatedly washed with ethanol, and dried to obtain a composite porous framework material;
[0098] 9) 3 g of the composite porous skeleton material was dispersed in 200 mL of a mixed solution composed of anhydrous ethanol and deionized water in a volume ratio of 3.5:1, and then 15 g of the composite fiber material was added. After ultrasonic treatment at 400 W for 25 min, the mixture was condensed and refluxed at 92 °C for 25 min. The precipitate was collected by vacuum filtration, repeatedly washed with ethanol, and then dried to obtain a hollow nanocage fiber material.
[0099] Example 3
[0100] A method for resource utilization of fluorine-containing sludge in photovoltaic wastewater, the specific method is as follows:
[0101] S1 adds calcium hydroxide to the sludge of photovoltaic wastewater, stirs it to make it fully mixed, and obtains pretreated sludge;
[0102] The amount of calcium hydroxide added is 12% of the total mass of the sludge;
[0103] S2 prepares the pretreated sludge into pulp, and then mixes and stirs it with a capture agent, a foaming agent and a regulator for flotation treatment;
[0104] The mass ratio of the capture agent, foaming agent and regulator is 2.3:1:0.9;
[0105] The capture agent accounts for 0.3% of the mass of the pretreated sludge dry basis;
[0106] Flotation treatment, temperature 42 °C, flotation time 12 min;
[0107] S3 The calcium fluoride sludge obtained by flotation is mixed with a hydrochloric acid solution to remove impurities soluble in the acid solution, and then neutralized with an alkali solution to obtain calcium fluoride sludge;
[0108] The mass ratio of calcium fluoride sludge to hydrochloric acid solution is 1:5;
[0109] S4: after mixing and grinding the concrete slag, the concrete slag is fully mixed with calcium fluoride sludge, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and water, extruded into a shape, dried and then baked at high temperature to obtain a building brick;
[0110] The mass ratio of calcium fluoride sludge, concrete slag, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and water is 80:30:18:50:7:9:18:15.
[0111] The preparation method of the hollow nano cage fiber material is as follows:
[0112] 1) 1.8 g of zinc chloride, 6.5 g of indium chloride tetrahydrate and 3.6 g of thioacetamide were dissolved in 800 mL of deionized water, stirred thoroughly and transferred to a reactor, reacted at 186° C. for 15 h, cooled to room temperature, and the product was repeatedly washed with deionized water and anhydrous ethanol, and dried to obtain flower-ball-shaped zinc thioindate;
[0113] 2) 5 g of zinc thioindate and 1.2 g of nano-titanium dioxide were dispersed in 800 mL of deionized water, subjected to 300 W ultrasonic dispersion for 50 min, and then mechanically stirred at 800 r / min for 5 h. After centrifugation, the mixture was repeatedly washed with deionized water and anhydrous ethanol, and then calcined at 165 ° C for 3 h to obtain composite nanoparticles with a hydrangea-like structure.
[0114] 3) 150 mL of anhydrous ethanol was measured and placed in a container, 18 mL of deionized water and 13 mL of glacial acetic acid were added, and the container was placed on a magnetic stirrer. While stirring, 3 mL of KH570 was added dropwise for a 50-min hydrolysis reaction. After the reaction was completed, 3 g of composite nanoparticles were added and reacted at 75° C. for 8 h. After the reaction was completed, the product was repeatedly centrifuged and washed with anhydrous ethanol, and vacuum dried at 65° C. for 18 h to obtain modified composite nanoparticles;
[0115] 4) Add 20 g of polyacrylonitrile to 200 mL of N, N-dimethylformamide, stir at 200 r / min for 6 h at room temperature, then add 2 g of polypyrrole, continue stirring for 52 h, then add 2 g of modified composite nanoparticles, mix thoroughly to obtain a spinning solution, then perform electrostatic spinning under the conditions of an electrostatic voltage of 24 kV, a receiving distance of 18 cm, and a propulsion rate of 3 mL / h, and after drying, perform carbonization treatment at 800 ° C for 3 h under nitrogen protection to obtain a nanofiber material;
[0116] 5) 12 mL of titanium tetrachloride with a concentration of 100 mmol / L was added to 160 mL of deionized water, and then 6 g of nanofiber material was repeatedly washed and dried with distilled water, acetone and ethanol, and then added thereto, treated in a 75° C. water bath for 50 min, and then placed in a muffle furnace and calcined at 560° C. for 50 min to obtain a pretreated nanofiber material;
[0117] 6) Add 2.8 mL of tetrabutyl titanate to 80 mL of concentrated hydrochloric acid, then add 80 mL of distilled water, stir thoroughly, add 5 g of pretreated nanofiber material, place in a reactor, stir at 80 r / min and react at 160 ° C for 5 h, cool to room temperature after the reaction, wash repeatedly with distilled water and anhydrous ethanol and dry, place in a muffle furnace, and calcine at 560 ° C for 50 min to obtain a composite fiber material;
[0118] 7) 2 mol of cobalt nitrate hexahydrate and 8 mol of 2-methylimidazole were dissolved in 260 mL of methanol respectively. After dissolution, the two were quickly mixed and stirred at 500 r / min for 50 min. After standing at room temperature for 28 h, the precipitate was collected by vacuum filtration, and repeatedly washed with methanol, and vacuum dried at 80° C. overnight to obtain a porous skeleton material;
[0119] 8) 10 g of the porous framework material and 20 g of nickel nitrate hexahydrate were dispersed in 180 mL of anhydrous ethanol respectively, stirred thoroughly and then quickly mixed, placed in a reaction kettle, reacted at 125° C. for 5 h, cooled to room temperature after the reaction was completed, the product was collected by vacuum filtration, repeatedly washed with ethanol, and dried to obtain a composite porous framework material;
[0120] 9) 5 g of the composite porous skeleton material was dispersed in 260 mL of a mixed solution composed of anhydrous ethanol and deionized water in a volume ratio of 4:1, and then 18 g of the composite fiber material was added. After ultrasonic treatment at 500 W for 30 min, the mixture was condensed and refluxed at 95 ° C for 30 min. The precipitate was collected by vacuum filtration, repeatedly washed with ethanol, and then dried to obtain a hollow nanocage fiber material.
[0121] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain hollow nanocage fiber material.
[0122] Comparative Example 2: This comparative example is basically the same as Example 1, except that in the preparation of the hollow nanocage fiber material, an equal amount of nano-titanium dioxide is used to replace the composite nanoparticles.
[0123] Comparative Example 3: This comparative example is basically the same as Example 1, except that in the preparation of the hollow nanocage fiber material, steps 1) to 3) are omitted.
[0124] Comparative Example 4: This comparative example is basically the same as Example 1, except that in the preparation of the hollow nanocage fiber material, steps 4) to 6) are omitted.
[0125] Comparative Example 5: This comparative example is basically the same as Example 1, except that in the preparation of the hollow nanocage fiber material, steps 7)-9) are omitted.
[0126] Test experiment:
[0127] After treating the wastewater of a photovoltaic factory containing 150 mg / L of fluoride in the water body, the fluoride-containing sludge obtained was processed into building bricks using the methods provided in Examples 1-3 and Comparative Examples 1-5, and then the strength of the bricks was tested. At the same time, each building brick was placed under a sprinkler head and rinsed with water at 60°C. The precipitation was controlled to be 20 mm / h and the rinse was continued for 120 hours. Then, the rinse water of each building brick was tested to detect the fluoride content in the rinse water. The statistical results are shown in Table 1.
[0128] Table 1
[0129]
[0130]
[0131] It can be seen from Table 1 that in the present invention, the building bricks obtained by resource utilization of fluorine-containing sludge have high compressive strength and can meet normal use. At the same time, under the flushing of water flow, no fluorine will overflow, no pollution to the environment, and it is safe and environmentally friendly.
[0132] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for resource utilization of fluorine-containing sludge from photovoltaic wastewater, characterized in that: The specific method is as follows: S1 adds calcium hydroxide to the sludge of photovoltaic wastewater, stirs it to make it fully mixed, and obtains pretreated sludge; The amount of calcium hydroxide added is 8-12% of the total mass of the sludge; S2 prepares the pretreated sludge into pulp, and then mixes and stirs it with a capture agent, a foaming agent and a regulator for flotation treatment; The mass ratio of the capture agent, the foaming agent and the regulator is (2.0-2.3):1:(0.7-0.9); The capture agent accounts for 0.1-0.3% of the mass of the pretreated sludge dry basis; The flotation treatment has a temperature of 36-42°C and a flotation time of 6-12 minutes; S3 The calcium fluoride sludge obtained by flotation is mixed with a strong acid solution to remove impurities soluble in the acid solution, and then neutralized with an alkali solution to obtain calcium fluoride sludge; The strong acid solution is any one of hydrochloric acid and sulfuric acid; The mass ratio of the calcium fluoride sludge to the strong acid solution is 1:(3-5); S4: after mixing and grinding the concrete slag, the concrete slag is fully mixed with calcium fluoride sludge, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and water, extruded into a shape, dried and then baked at high temperature to obtain a building brick; The mass ratio of the calcium fluoride sludge, concrete slag, high molecular polymer, cement, water reducing agent, nano titanium dioxide, hollow nano cage fiber material and water is (50-80): (20-30): (10-18): (40-50): (3-7): (5-9): (10-18): (8-15).
2. The method for resource utilization of fluorine-containing sludge from photovoltaic wastewater according to claim 1, characterized in that: The capture agent is at least one of oleic acid, sodium alkyl sulfate, and sodium cyclopentaneate; The foaming agent is at least one of pine oil, methyl isobutyl carbinol and butyl ether oil; The regulator is composed of calcium chloride, acidified water glass, sodium carbonate and polyacrylamide in a mass ratio of 1: (0.2-0.4): (0.5-0.8): (0.6-0.9); The high molecular polymer is composed of EVA emulsion and water-based chloroprene rubber in a mass ratio of 1: (1.0-1.3).
3. The method for resource utilization of fluorine-containing sludge from photovoltaic wastewater according to claim 1, characterized in that: The high temperature baking has the following temperature conditions: the starting temperature is room temperature, which is raised to 800-860°C at a rate of 10-13°C / min, kept at that temperature for 30-50min, then lowered to 320-340°C at a rate of 12-15°C / min, and then cooled naturally.
4. The method for resource utilization of fluorine-containing sludge from photovoltaic wastewater according to claim 1, characterized in that: The hollow nano cage fiber material is prepared by the following method: 1) Dissolving cobalt nitrate hexahydrate and 2-methylimidazole in methanol respectively, mixing the two rapidly after dissolution, stirring for 30-50 minutes, and then standing at room temperature for 24-28 hours, collecting the precipitate by vacuum filtration, and repeatedly washing with methanol, and drying to obtain a porous skeleton material; 2) The porous skeleton material and nickel nitrate hexahydrate are dispersed in anhydrous ethanol respectively, stirred sufficiently and then quickly mixed, placed in a reaction kettle, reacted at 120-125° C. for 2-5 hours, cooled to room temperature after the reaction is completed, the product is collected by vacuum filtration, repeatedly washed with ethanol, and dried to obtain a composite porous skeleton material; 3) dispersing the composite porous skeleton material in the mixed solution, adding the composite fiber material, ultrasonically treating for 20-30 minutes, condensing and refluxing at 90-95° C. for 20-30 minutes, collecting the precipitate by vacuum filtration, repeatedly washing with ethanol and drying, and then obtaining the hollow nanocage fiber material.
5. The method for resource utilization of fluorine-containing sludge from photovoltaic wastewater according to claim 4, characterized in that: The ratio of cobalt nitrate hexahydrate, 2-methylimidazole and methanol is (1-2) mol: (4-8) mol: (150-260) mL; The ratio of the porous skeleton material, nickel nitrate hexahydrate and anhydrous ethanol is (5-10) g: (10-20) g: (120-180) mL; The ratio of the composite porous skeleton material, the mixed solution, and the composite fiber material is (2-5) g: (150-260) mL: (10-18) g; The mixed solution is composed of anhydrous ethanol and deionized water in a volume ratio of (3-4):
1.
6. The method for resource utilization of fluorine-containing sludge from photovoltaic wastewater according to claim 1, characterized in that: The composite fiber material is prepared by the following method: 1) Adding polyacrylonitrile to N,N-dimethylformamide, stirring at room temperature for 4-6 hours, then adding polypyrrole, continuing stirring for 48-52 hours, then adding modified composite nanoparticles, fully mixing to obtain a spinning solution, then electrospinning, drying, and carbonizing at 700-800° C. for 2-3 hours under nitrogen protection to obtain a nanofiber material; 2) adding titanium tetrachloride to deionized water, then adding the nanofiber material after repeated washing and drying with distilled water, acetone and ethanol, treating in a 70-75° C. water bath for 30-50 min, then placing in a muffle furnace, calcining at 500-560° C. for 30-50 min, to obtain a pretreated nanofiber material; 3) Add tetrabutyl titanate to concentrated hydrochloric acid, then add distilled water, stir thoroughly, add pretreated nanofiber material, place in a reactor, stir at 50-80 r / min at 150-160° C. for 3-5 hours, cool to room temperature after the reaction, wash repeatedly with distilled water and anhydrous ethanol, dry, place in a muffle furnace, and calcine at 500-560° C. for 30-50 minutes to obtain a composite fiber material.
7. The method for resource utilization of fluorine-containing sludge from photovoltaic wastewater according to claim 6, characterized in that: The ratio of polyacrylonitrile, N,N-dimethylformamide, polypyrrole, and modified composite nanoparticles is (10-20) g: (100-200) mL: (1-2) g: (1-2) g; The electrospinning process is carried out under the following conditions: electrostatic voltage 18-24 kV, receiving distance 15-18 cm, and propulsion rate 2-3 mL / h.
8. The method for resource utilization of fluorine-containing sludge from photovoltaic wastewater according to claim 6, characterized in that: The ratio of titanium tetrachloride, deionized water and nanofiber material is (8-12) mL: (100-160) mL: (3-6) g; The titanium tetrachloride has a concentration of 80-100 mmol / L; The ratio of tetrabutyl titanate, concentrated hydrochloric acid, distilled water and pretreated nanofiber material is (1.5-2.8) mL: (50-80) mL: (50-80) mL: (2-5) g.
9. The method for resource utilization of fluorine-containing sludge from photovoltaic wastewater according to claim 1, characterized in that: The modified composite nanoparticles are prepared by the following method: 1) Dissolve zinc chloride, indium chloride tetrahydrate and thioacetamide in deionized water in sequence, transfer to a reaction kettle after sufficient stirring, react at 180-186° C. for 10-15 hours, cool to room temperature, wash the product repeatedly with deionized water and anhydrous ethanol in sequence, and dry to obtain zinc thioindate; 2) Dispersing zinc thioindate and nano titanium dioxide in deionized water, ultrasonically dispersing for 30-50 minutes, mechanically stirring for 3-5 hours, centrifuging, washing repeatedly with deionized water and anhydrous ethanol, and then calcining at 160-165° C. for 2-3 hours to obtain composite nanoparticles; 3) Anhydrous ethanol is measured and placed in a container, deionized water and glacial acetic acid are added, and the container is placed on a magnetic stirrer. KH570 is added dropwise while stirring for a hydrolysis reaction of 30-50 minutes. After the reaction is completed, the composite nanoparticles are added and reacted at 70-75° C. for 6-8 hours. After the reaction is completed, the product is repeatedly centrifuged and washed with anhydrous ethanol, and then dried to obtain modified composite nanoparticles.
10. The method for resource utilization of fluorine-containing sludge from photovoltaic wastewater according to claim 9, characterized in that: The ratio of zinc chloride, indium chloride tetrahydrate, thioacetamide and deionized water is (1.3-1.8) g: (5.8-6.5) g: (3.0-36.) g: (600-800) mL; The ratio of the zinc thioindate, nano-titanium dioxide and deionized water is (2-5) g: (0.5-1.2) g: (500-800) mL; The ratio of anhydrous ethanol, deionized water, glacial acetic acid, KH570 and composite nanoparticles is (100-150) mL: (10-18) mL: (8-13) mL: (2-3) mL: (2-3) g.
Citation Information
Patent Citations
Preparation method of novel metal organic complex fibers and derivative porous carbon fibers thereof
CN105862174A
Method for making shale bricks with calcium fluoride sludge and treatment method of fluorine-containing wastewater
CN106365610A
Method for preparing sludge with strongly-acidic fluorine-containing waste water to prepare calcium fluoride concentrate
CN109399687A
Preparation method of indium zinc sulfide-titanium dioxide composite material and application of indium zinc sulfide-titanium dioxide composite material in production of hydrogen peroxide for wastewater treatment
CN113663693A
Preparation method of titanium dioxide battery negative electrode material and product thereof
CN113948695A
